Theory of religious cycles : tradition modernity and the Bahá'í faith - Sergeev, Mikhail (Value Inquiry Book Series, 2015)
In Theory of Religious Cycles: Tradition, Modernity and the Bahá'í Faith Mikhail Sergeev offers a new interpretation of the Soviet period of Russian history as a phase within the religious evolution of humankind by developing a theory of religious cycles, which he applies to modernity and to all the major world faiths of Judaism, Buddhism, Christianity, and Islam. Sergeev argues that in the course of its evolution religion passes through six common phases-formative, orthodox, classical, reformist, critical, and post-critical. Modernity, which was started by the European Enlightenment, represents the critical phase of Christianity, a systemic crisis that could be overcome with the appearance of new religious movements such as the Bahá'í Faith, which offers a spiritual extension of the modern worldview.